Pacha Mama eco turística para la región de Oriente: Ecoparque de conectividad urbana (2017)
Development of an urban and architectural project in the municipality of Choachí - Cundinamarca, starting with the proposal of a partial plan at the city level region, where the environmental impact of the development of one of the 4G concessions being built at the national level is minimized. The same way is intended to strengthen and enhance the local economy, through the integration of natural elements that are a great potential of the municipality. With the development of an analysis of the place and generating a diagnosis is intended to create solutions to the main social, functional and environmental problems, respecting in an integral way the natural patrimony of the sector and strengthening the existing ones. Generates a public - private project, which is developed at the level, urban (public space), and aesthetic, architectural, functional, structural, bioclimatic and technical. The main theme of the project is ecological culture and tourism, which aims to educate, educate and sensitize people about the importance of nature in the human life cycle.